Head to toe - Pangan, Margarita Gianina M. (Animo Repository, 2021)
The project, entitled Head to Toe is a 9-image conceptual photo essay about the body policing Filipino women face in the Philippines. It is grounded on the theory of the Male Gaze by Laura Mulvey along with the post-feminist sensibility of Rosalind Gill. The Male Gaze argues that the media positions women to be objectified. On the other hand, the post-feminist sensibility (which is not akin to the feminist movement) states we must view the world in a way that feminist and anti-feminist notions are present together— working against each other. To illustrate the concept, I decolonized the idea of the Male Gaze and the post-feminist sensibility to fit Filipino culture. Through a collaboration with 10 Filipino women who wished to express their sentiments regarding body policing and the like, I was able to build the narrative for the photographs. This collaboration included at least one hour of [individual] interviews wherein the women shared their stories, and a two hour conceptualization session to agree with how these stories will be visually represented. The photographs are meant to represent how the gaze operates and the common phrases used to belittle women and impose patriarchal standards. I intend to aid Filipino women in confronting what the Male Gaze in a post-feminist Philippine society is, and show them they are neither alone alone nor in the wrong. I conceptualized and produced this project, which I then post-processed using Adobe Lightroom Classic and Adobe Photoshop. The web page layout was created and hosted on the platform Cargo Collective.